The mystery of the "simple object" in Wittgenstein’s Tractatus - Danko, Sofia V. (Вестник Томского государственного университета. Философия. Социология. Политология)
The concept of the object in the Tractatus Logico-Philosophicus is still a mystery to scholars. It is yet unclear whether the object is a physical quality, a universal, a Platonic form, an abstract metaphysical construct, etc. There is still no consensus either on how the object relates to the name in the proposition and how the object, while remaining “simple”, determines all logically possible events. This is only a small part of the questions that researchers have in connection with this concept. The article proposes a detailed reconstruction of the “logical structure” presented in the Tractatus and puts forward a version of the answer to the question: What is a simple object?